(untitled) - Blass, Laurie (Boston, 2007)
Quest Second Edition parallels and accelerates the process native-speaking students go through when they prepare for success in a variety of academic subjects. Quest helps students get "up to speed" in terms of both academic content and language skills.. The four Listening and Speaking books in the Quest series contain listening and speaking strategies and practice activities centered on authentic recordings from "person on the street" interviews, social conversations, radio programs, and university lectures..
Keywords: English language,English language,Tiếng Anh,Tiếng Anh; Textbooks for foreign speakers,Spoken English,Problems, exercises, etc.,Giáo trình dành cho người nước ngoài,Tiếng Anh giao tiếp,Bài tập và bài giải